Analysis Physical Condition of The Position Women’s Basketball Players Perennial Foundation Of Perbaspa Kediri District - Florensa, Yohana Cindi; Hariadi, Imam; Yunus, Moch.; Hanief, Yulingga Nanda (STKIP PGRI Jombang, 2023)
This study aims to determine: (1) physical condition of arm muscle strength, (2) speed, (3) agility, (4) leg muscle power, (5) endurance, (6) physical condition of women's basketball players Perbaspa Perbaspa Foundation Kediri Regency based on player position. This type of research is quantitative descriptive research with data collection techniques using survey methods with test and measurement techniques. The population in this study were all female basketball players at the Perbaspa Abadi Foundation, Kediri Regency, consisting of 15 players. The sampling technique in this study is total sampling. The test instruments used were the push up test, 30 meter sprint, dogging run, vertical jump and multistage fitness test. The results showed that the physical condition of women's basketball players at the Abadi Perbaspa Foundation, Kediri Regency in the components of arm muscle strength, 12 players (80%) were in the poor category, the speed of 5 players (33%) was in the medium category, the agility of 15 players (100%) was in the very category. good, leg muscle power of 11 players (73%) is in the poor category, endurance of 13 players (87%) is in the very poor category. The results of the physical condition based on the player's position show that the dominant physical condition of the point guard position (PG1) is speed and agility, the shooting guard position (SG2) speed and agility, small forward agility (SF3), power forward position (PF4) arm muscle strength, speed and agility, middle position (C5) speed and agility. Physical condition is one aspect that cannot be underestimated, because basketball players have positions and tasks where each task requires different components of physical condition, so coaches need to know what physical components are needed to improve performance.